-5(x+4)=7-(-5)

Simple and best practice solution for -5(x+4)=7-(-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(x+4)=7-(-5) equation:


Simplifying
-5(x + 4) = 7 + -1(-5)

Reorder the terms:
-5(4 + x) = 7 + -1(-5)
(4 * -5 + x * -5) = 7 + -1(-5)
(-20 + -5x) = 7 + -1(-5)

Multiply -1 * -5
-20 + -5x = 7 + 5

Combine like terms: 7 + 5 = 12
-20 + -5x = 12

Solving
-20 + -5x = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '20' to each side of the equation.
-20 + 20 + -5x = 12 + 20

Combine like terms: -20 + 20 = 0
0 + -5x = 12 + 20
-5x = 12 + 20

Combine like terms: 12 + 20 = 32
-5x = 32

Divide each side by '-5'.
x = -6.4

Simplifying
x = -6.4

See similar equations:

| (3+2i)(4+3i)= | | -3x+8=2x+3 | | (3/y)+(2/5)=19/20 | | 6x^2+4x=21 | | -7(2x+8)=14 | | 8z+22=3(3z+11)z | | 11x-3x=400 | | (x^4)-(5x^2)+(4)=0 | | 6(2/3x-7/6)=6*7/2 | | -2y-1=4x+3 | | b+9=24 | | 23x=173 | | 4(x+19)=3x+41 | | y=-4y+1 | | 2(-.26)+7.5=6.2-3(-.26) | | 13x+21=47 | | 3a+7b=1650 | | f(t)=2.25+0.75x | | 4+x=4x-23 | | 0.2c-0.6+.5c=5 | | 3(6+8)=24+18x | | 10m^2-6=404 | | -11.1-2.2x=2.2x/7.7-2x-x^2 | | x^3+5x^2-5x-25=0 | | 1x-2=6x+5 | | (3a+19)+2z= | | 5w+2=w+10 | | x-200=.2x | | x(x+8)(x+7)=0 | | 2r+3u=2(3r+6) | | -2(x+5)=4-(-5) | | 4x-20=3x+15 |

Equations solver categories